Hybrid nanoparticles with ethylene glycol for car radiator application - Kadirgama, Kumaran
This project is about Aluminium Oxide (Al₂O₃) nanoparticles with Ethylene Glycol for car radiator application. The research is conducted in order to prove that addition of Al₂O₃ nanoparticles with varying concentration provides a better heat transfer efficiency compared to usage of distilled water as radiator coolant. The objective of the research is to improve and create a new radiator coolant based on collaboration of Al2O3 nanoparticles with readily available coolants which is Ethylene Glycol and to investigate the erosion of Al₂O₃ nanoparticles coolant on automotive radiator. The scopes of the research are the nanoparticles used in the experiment is Al₂O₃ nanoparticles between ranges of size 40-80 nm. The tested concentration of Al₂O₃ nanofluids are as of 0.01%, 0.03%, 0.05%, 0.07% and 0.09%. The preparation of Al₂O₃ nanofluids are carried out Thermodynamics Laboratory of Universiti Malaysia Pahang. The experiment is carried out by running the radiator test rig with distilled water as radiator coolant. This is done so that the result obtained through experimental analysis of distilled water can be used as bench mark to for the comparison of heat transfer efficiency. The thermal coefficient test indicates that all the Aluminium Oxide (Al₂O₃) nanofluid with varying concentration possess better heat conducting properties compared to Ethylene Glycol. Furthermore, this proves that Aluminium Oxide (Al₂O₃) nanofluids can transfer the absorbed heat from the radiator to the surrounding air much faster compared to Ethylene Glycol. Experimental analysis shows that Al₂O₃ nanofluids have higher specific heat capacity compared to distilled water. Thus, Al₂O₃ nanofluids can absorb and store more heat compared to distilled water. Heat transfer coefficient result supports that application of Al₂O₃ nanofluids as car radiator coolant leads to increase in thermal absorption enhancement. However, as the concentration of Aluminium Oxide (Al₂O₃) nanofluid increase from 0.03% to 0.05% and so on, the heat transfer coefficient decreases rapidly. This is because formation of sediments of Aluminium Oxide (Al₂O₃) nanoparticles causes inactive involvement in heat transfer process but the sediments do no clogs in the flat tubes or trigger erosion on the internal wall of car radiator. It can be concluded that application of Aluminium Oxide (Al₂O₃) nanoparticles integrated with Ethylene Glycol as coolant in car radiator is acceptable and provides better heat transfer efficiency.